Some Properties of Convex Fuzzy Compact Spaces - Daher, Hawraa Yousif; Kider, Jehad R. (Iraqi Journal of Science, 2025)
The first goal in this paper is using the definition of convex fuzzy normed space to present the definition of convex fuzzy compact space. After that an example is introduced to improve the existence of such space. The second aim is to introduce important concepts and prove properties of convex fuzzy compact space. Moreover, we proved if  is convex fuzzy compact then  is totally convex fuzzy bounded, as well as we prove if  is convex fuzzy compact then   is convex fuzzy complete.